Réponses

2014-10-16T06:11:44+02:00
Ex 4:
A= -4- 3*25 +1*36 = -4 -75 +36 = -43
B= \frac{ 3^{3} * 7^{4} *( 3^{2} )^{3}}{ 3^{8} *( 7^{2} )^{2} }
   =\frac{ 3^{3} * 7^{4} *(3^{2*3}) }{ 3^{8} *( 7^{2*2}) }
   =\frac{ 3^{3} * 7^{4} *3^6 }{ 3^{8} * 7^{4} }
   =\frac{ 3^{3+6}}{ 3^{8} }
   =\frac{ 3^{9}}{ 3^{8} }
   = 3
C=  (\frac{2}{3} )^{3} x (- \frac{4}{3} )^{-2}
   =\frac{2^{3} }{3^{3} } x \frac{(-4)^{-2} }{3^{-2} }
   =\frac{2^{3} }{3^{3} } x \frac{2^{-4} }{3^{-2} }
   =\frac{2^{-1} }{3} = \frac{1}{6}
D=(-\frac{5}{8})^{8} x (-\frac{25}{9})^{-4} =(\frac{5}{8})^{8}x(\frac{25}{9})^{-4} =\frac{5^{8} }{8^{8} }x \frac{5^{8} }{3^{-8} }=\frac{5^{16}* 3^{8}  }{8^{8} }=\frac{25^{8}* 3^{8}  }{8^{8} }= (\frac{75}{8} )^{8}
Ex 5:
A=[tex](3a^{4} b^{3} )x(8 ab^{2} )=24 a^{5} b^{5} [/tex]
B=[tex] (2a^{4} )^{4} * a^{-5} = 2^{4} a^{16} * a^{-5} =16 a^{11} [/tex]
C=[tex](6a^{5} b^{3} )^{2} * (ab)^{-7} = 6^{2} a^{10} b^{6} a^{-7} b^{-7} =36 a^{3} b^{-1} = \frac{36 a^{3} }{b} [/tex]